Vertical integration and value-relevance: Empirical evidence from oil and gas producers - Bård Misund (Cogent Economics & Finance, 2016)
Oil and gas exploration companies (E&Ps) exhibit large variations in earnings due to volatile oil and gas prices. Furthermore, their primary asset, oil and gas reserves, is accumulated through highly risky exploration activities. In contrast, integrated oil and gas companies display lower variability in their earnings due a more diversified asset base. The literature suggests that companies with higher earnings volatility and higher levels of intangibles among their assets should have lower value relevance of accounting information than companies with higher levels of tangible assets on their balance sheets. For that reason, E&P companies should have lower value relevance than integrated companies. Contrary to expectations, we do not find lower value relevance for E&Ps earnings than integrated oil and gas companies. In fact, the results suggest that the presence of supplementary estimates for oil and gas reserves values mitigate the potential problem associated with the presence of intangible assets experienced in other industries.
Keywords: M21; M40; G12; Q49; 330; company valuation; value-relevance; oil and gas industry; vertical integration; valuation; oil majors; oil integrateds; exploration & production; E&P